Evaluating the Sustainability of Community-Based Water Supply Systems: Insights from the Deurali-Hupsekot Urban Water Supply and Sanitation Project, Gandaki Province, Nepal - K.C., Bishal; Baniya, Arjun; Poudyal, Ramhari; Awasthi, Keshab D.; Baniya, Mahendra B.; Gautam, Arjun; Pandit, Kul C. (Himalayan Journal of Applied Science and Engineering, 2025)
Sustainable water supply entails finding reliable and resilient methods to meet human water needs without depleting sources, harming the local economy, or causing environmental damage. Community-based water supply systems play a vital role in decision-making, operation, and maintenance, promoting ownership and sustainability. This research assesses the sustainability of a community-based water supply and sanitation project, focusing on technical performance, institutional arrangements, and socio-economic conditions. This study includes qualitative and quantitative research and household sampling of 230 respondents. To determine the weight of factors and subfactors influencing sustainability, the report employs the Analytical Hierarchy Process (AHP), a widely recognized decision-making tool. The project demonstrates a high level of sustainability (91.46%) in terms of technical dimension with moderate sustainability (61.19%) in the institutional and socio-economic aspects. The project achieves a sustainability rating of 69.48% in operation and maintenance. The income trends indicate potential for loan repayment and financial sustainability, while sufficient human resource ensures the smooth functioning and maintenance of the infrastructure. Overall, the project achieves a commendable sustainability rate of 79.89%. The findings from the study provide valuable insights for project implementers, policymakers, and stakeholders involved in similar community-based water supply and sanitation initiatives, promoting sustainable development and improved water access for the community.